Effects of Selective α7 Nicotinic Acetylcholine Receptor Stimulation in Oligodendrocytes: Putative Implication in Neuroinflammation - Claudia Guerriero; Giulia Puliatti; Tamara Di Marino; Giulia Scanavino; Carlo Matera; Clelia Dallanoce; Ada Maria Tata (Cells, 2025)
α7 nAChRs are known to modulate several physiological and pathological functions in glial cells, and their selective activation might have anti-inflammatory effects in the central and peripheral nervous system. OL progenitors (OPCs) respond to cholinergic stimuli via muscarinic receptors that are mainly involved in the modulation of their proliferation. Conversely, the role of nicotinic receptors, particularly α7 nAChRs, has been poorly investigated. In this study, we evaluated the expression of α7 nAChRs in a model of OPCs (Oli neu) and the potential effects mediated by their selective activation. Methods: Oli neu cells were used as a murine immortalized OPCs model. The effects of α7 nAChRs stimulation on cell proliferation and survival were assessed by the MTT assay. RT-PCR and Western blot analysis were used to analyze the expression of α7 nAChRs and proliferative and differentiative markers (PCNA, MBP). LPS exposure was used to induce the environment in which the antioxidant and anti-inflammatory properties of α7 nAChRs were analyzed, evaluating NFR2 and TNF-α expression, ROS levels through DCFDA staining while Oil Red O staining was used for the analysis of lipid droplet content as a marker of cellular inflammation response. Results: The α7 nAChR is expressed both in OPCs and OLs, and its stimulation by the selective agonist ICH3 increases cell proliferation without modifying the OLs’ differentiation capability. Moreover, ICH3 showed anti-inflammatory and antioxidant effects against LPS exposure. Conclusions: The results herein obtained confirm the role of α7 nAChR in the modulation of neuroinflammatory processes as well as their protective effects on OLs.